Conserved Autophagy Pathway Contributes to Stress Tolerance and Virulence and Differentially Controls Autophagic Flux Upon Nutrient Starvation in Cryptococcus neoformans - Zhao, Xueru; Feng, Weijia; Zhu, Xiangyang; Li, Chenxi; Ma, Xiaoyu; Li, Xin; Zhu, Xudong; Wei, Dongsheng (Frontiers in Microbiology, 2019)
Autophagy is mainly a catabolic process, which is used to cope with nutrient deficiency and various stress conditions. Human environment often imposes various stresses on Cryptococcus neoformans, a major fungal pathogen of immunocompromised individuals; therefore, autophagic response of C. neoformans to these stresses often determines its survival in the host. However, a systematic study on how autophagy related (ATG) genes influence on autophagic flux, virulence, stress response and pathogenicity of C. neoformans is lacking. In this study, 22 ATG-deficient strains were constructed to investigate their roles in virulence, pathogenesis, stress response, starvation tolerance and autophagic flux in C. neoformans. Our results showed that Atg6 and Atg14-03 significantly affect the growth of C. neoformans at 37°C and laccase production. Additionally, atg2Δ and atg6Δ strains were sensitive to oxidative stress caused by hydrogen peroxide. Approximately half of the atgΔ strains displayed higher sensitivity to 1.5 M NaCl and remarkably lower virulence in the Galleria mellonella model than the wild type. Autophagic flux in C. neoformans was dependent on the Atg1-Atg13, Atg5-Atg12-Atg16, and Atg2-Atg18 complexes and Atg11. Cleavage of the green fluorescent protein (GFP) from Atg8 was difficult to detect in these autophagy defective mutants; however, it was detected in the atg3Δ, atg4Δ, atg6Δ and atg14Δ strains. Additionally, no homologs of Saccharomyces cerevisiae ATG10 were detected in C. neoformans. Our results indicate that these ATG genes contribute differentially to carbon and nitrogen starvation tolerance in C. neoformans compared with S. cerevisiae. Overall, this study advances our knowledge of the specific roles of ATG genes in C. neoformans.